Punishment: The Civil Perspective of Punitive Damages - Kuklin, Bailey (1989)
Punitive, or exemplary damages, have been recognized in the Anglo-American common law systems for two centuries. This Article explores the consequences of treating punitive damages as a private means of punishment. Light is shed on the controversies surrounding, first, the attempt to adopt a standard of punishment, private or public, and second, to apply such a standard. The concentration on punitive damages for this exploratory undertaking, instead of criminal sanctions, avoids the need to account for additional imputed public penal purposes, such as rehabilitation and isolation. As a preliminary matter, the emphasis of this Article should be made clear. The concern here is essentially with a version of Hart's third question. Assuming that punitive damages are justifiable, and the defendant before the court is properly to be assessed these extraordinary damages, how much is that award to be? In pursuing this task, some common understandings of punishment are modeled. If the models cohere into a unified monetary judgment, this eases the pressure on courts to clearly articulate, pursuant to Hart's first question, the justification for punitive damages. Understanding the proper rationale, or compromises, is of less abiding importance to the extent that the ultimate award is unaffected. Furthermore, clear thinking on the measurement may clarify the problems regarding Hart's second question of who should suffer the punishment. Finally, the jury instructions, which reflect the application of the answer to Hart's third question, may be refined if all models lead to a similar measurement. In the end, punitive damages, and punishment more generally, can neither be justified nor implemented beyond debate. My conclusion, nevertheless, is that a place remains for punitive damages